Tinjauan Hukum terhadap Upaya Perlindungan Investor dalam Pengelolaan Dana Investasi di Sektor Real Estate (DIRE) (Jurnal Sosial Humaniora dan Pendidikan, 2025)
Real Estate Investment Trusts (REITs), known in Indonesia as Dana Investasi Real Estat (DIRE), are collective investment instruments that have rapidly developed in Indonesia's capital market and serve as an alternative financing source in the property sector. DIRE enables the public to invest indirectly in real estate assets through Collective Investment Contracts managed by Investment Managers and held by Custodian Banks. Despite offering liquidity and attractive returns, DIRE carries inherent risks, particularly the risk of default by the investment manager. This research aims to examine, from a normative legal perspective, the extent of legal protection provided to DIRE investors as regulated and implemented under Indonesian law. Using a normative juridical method with a descriptive-analytical approach, the study utilizes secondary data including statutory regulations, legal literature, and academic journals. The findings indicate that legal protection for DIRE investors remains limited in effectiveness, as it is predominantly administrative and reactive in nature. Although regulations such as the Indonesian Civil Code, the Consumer Protection Act, and OJK Regulations No. 1/POJK.07/2013 and No. 19/POJK.04/2016 provide a legal basis, there is still a need to enhance preventive oversight, ensure faster dispute resolution, and establish clear compensation mechanisms. Therefore, strengthening prudential supervision, improving transparency, and increasing investor education are essential to ensure that legal protection functions optimally and substantively to uphold legal certainty in the real estate investment sector.